Die Frage des Strafvollzugs in der Bundesrepublik Deutschland im Spiegel des Spiegels (1947-1979) - Grégory Salle (Criminocorpus)
Founded in 1947, Der Spiegel has occupied a unique position within the German journalistic field (and more broadly in Europe) during the following decades. Read by millions of Germans, this renowned news weekly was not only synonymous with quality and editorial independence, but also with a critical journalism that showed no leniency towards the social elites. Revered as well as feared, it was sometimes criticized, but nevertheless, definitely remained the newspaper of record, especially during the 1950’s-1970’s. As the name suggests (“The Mirror”), Der Spiegel was then expected to reflect the reality of German society, if need be, by disclosing what went on behind the visible scenes. And what was more hidden than the prison life, which meant secrecy, censorship and opacity, especially in a historical moment where the subject of prisons was pushed to the margins of the public sphere, before being back in the forefront at the end of the 1960’s? This raises the question: how has the “prison issue” been dealt with by the most respected newspaper – and famous for its important revelations – at the time? This article, which draws on sources that are for the most part online available sources, describes the relevance as well as the limits of the discourse of Der Spiegel on the prison issue in West Germany during the 1950’s-1970’s.